2015
DOI: 10.1155/2015/613831
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasonography Features of Breast Malignancies with Different Sizes: Correlation with Prognostic Factors

Abstract: This study was to investigate the correlation between contrast-enhanced ultrasonography (CEUS) characteristics with prognostic factors in breast cancers with different sizes. A retrospective analysis of CEUS characteristics of 104 pathologically proven malignant lesions from 104 women was conducted. Lesions were divided into two groups according to their size measured by US (Group 1: maximum diameter ≤20 mm; Group 2: maximum diameter >20 mm). Features including enhancement degree, order and pattern, enlargemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“… 23 It was shown that c-erb-B2 was positive in 50.96% of malignant breast lesions, and the positive expression of this gene was associated with high enhancement in imaging. 24 The defects in vascular perfusion are common in ER-negative tumors. 24 Another study has shown that the concentric mode of enhancement was common in ER-negative tumors, and perfusion defects were generally seen in tumors with negative ER expression, positive c-erb-B2 expression, and positive Ki-67 expression, 25 which were consistent with this study.…”
Section: Discussionmentioning
confidence: 99%
“… 23 It was shown that c-erb-B2 was positive in 50.96% of malignant breast lesions, and the positive expression of this gene was associated with high enhancement in imaging. 24 The defects in vascular perfusion are common in ER-negative tumors. 24 Another study has shown that the concentric mode of enhancement was common in ER-negative tumors, and perfusion defects were generally seen in tumors with negative ER expression, positive c-erb-B2 expression, and positive Ki-67 expression, 25 which were consistent with this study.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, perfusion defects are the result of rapid growth and active metabolism of malignant tumors, leading to insufficient vascular formation and nutrition supply and finally to central hypoxia and necrosis (38). Moreover, Liu et al attribute perfusion defects to low cellularity, desmoplastic stroma, dilated duct, degeneration, fibrosis or necrosis (18). According to the literature, central necrosis and fibrosis are common in ER negative tumors (39,40), while regional hypoxia is associated with reduced ER expression in breast cancer patients (41).…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies in literature exploring correlation between CEUS characteristics and pathological prognostic factors in breast cancer patients during the last six years, indicating a novel research area (13)(14)(15)(16)(17)(18)(19). Also, these studies have shown mixed results and have had differences in patients' populations, study design, statistical analysis etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From the gained results it is obvious that smaller lesions could cause diagnostic problem. The problem with small lesions and CEUS examination tried to explain in their study Zhao et al They reported that lesions with different size expressed different CEUS features that are dependent on the neovascularisation [17], and this can cause a diagnostic ambiguity. Small lesions according Zhao (smaller than 20 mm) might have poor neovascularization due to slow growth, low grade or early stage of disease.…”
Section: Discussionmentioning
confidence: 99%